Escola para adultos uma valorização à vida - Coelho, Elizabeth Soares (2003)
The purpose of this research focuses the perception of the students of the Adults’ School: what it means to attend the classes and how the Methodist Church’s Mission is present in this Project, with the following northward Question: HOW DOES THE METHODIST CHURCH, THROUGH ITS MISSION, HELP TO IMPROVE THE LIVE OF PERSONS ABOVE 45 YEARS OLD? Originating from this Question, the following topics: How did students know about the performance of the Adults’ - School?Why did they start to attend it?- What modifications did occur in their lives, after becoming a member of the Adults’ School? And -If they recommend the Adults’ School to their friends and familiars. The participants of this research were chosen among the students of this Project, matriculated in the Adults’ School: one is a single woman, two married women, other separated and another widow; a teacher of the Adults’ School and three employees of the Centenário School (a woman and 2 men); the familiars of the students of the Adults’ School were represented by a daughter, a granddaughter and a spouse; a Methodist Church’s Pastor also took part in this research, totaling 13 persons, from 10 to 74 years old. Each member of this researched people was identified with the names of persons who dedicated their lives to the increase and development of the Centenário School’ History. This manner of identification was a way to pay a tribute to these edifying lives, who gave evidence of a great faith and planted the Seed of Love and Hope, that is alive, until today, in the Institution. In this study, together with some chapter’s titles of this research, were also utilized some terminologies used in the Liturgy of the Methodist Church’s cult, in order to make the Methodist Church being known and alsoto learn more about its Mission. In the Chapter of the Edification of the Literature Review, there is a Historical Retrospective of: the Methodism’s Origin, the Centenário School’s history and the Thanksgiving or the Methodist Aging. This research was based on the Phenomenology. The Method was the Descriptive The research’s approach was the Qualitative and the assumed Form was the study of the Ethnographic Case.In the collect of information, interviews and daily field were utilized and in the interpretation, a process of Content Analysis was made. In This study the information was taken in direct contact between the researcher and the interviewees. In the interviews the themes were: How did these students know about the performance of the Adults’ School; Why did they start to attend it and What modifications did appear after attending it and if they recommend the Adults’ School to their friends and familiars. In the Chapter of The Good New, there are registered speeches in which the interviewees expressed theirs thoughts. This research provided to the participants an opportunity to share their sadness and anxieties before attending the Adults’ School and the joy and the own rescue of the individual valuation and the pleasure to live in group, with the students of the Adults’ School.